المنهج الإبداعي في التفسير البياني: بنت الشاطئ أنموذجًا = Creative approach in linguistic interpretation: Bint Al-Shati’ as a case of study - Elatrash, Radwan Jamal Yousef; ., Lukmanul Hakim (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2019)
تهدف هذه المقالة إلى دراسة منهج بنت الشاطئ في تفسيرها، وبيان خطتها ومناقشتها من خلال كتابها التفسير البياني للقرآن الكريم. وهذه المقالة تعتمد على المنهج الاستقرائي؛ وذلك لاستقراء الآيات واطلاع البيانات المتعلقة ببنت الشاطئ من خلال تفسيرها. واستخدم الباحثان أيضًا المنهج التحليلي؛ وذلك لمناقشة المعلومات الواردة في هذه القضية، واستنباط منهج بنت الشاطئ في تفسيرها. ومن أهمّ النتائج التي توصل إليها الباحثان أن بنت الشاطئ قد حاولت تفسير القرآن الكريم متبعة أربعة مناهج وهي؛ التناول الموضوعي، وفهم ما حول النص، وفهم دلالات الألفاظ، وفهم أسرار التعبير. وهذا بلا شك منهج إبداعي قلَّ نظيره. ********************************************************* The present paper aims to study Bint al-Shati’s interpretation approach, explains and discusses her plan through her book At-Tafsīr al-Bayānī Li al-Qur’ān al-Karīm. The paper adopts the inductive approach, so as to extrapolate verses and find out about Bint al-Shāti’s interpretation. Also, the analytical approach is employed, so as to discuss information contained in the subject matter, and devise Bint al-Shati’s interpretation. The result shows that Bint al-Shati’ attempted to interpret the Qur’an based on four approaches, addressing the text objectively, understanding the meanings of the text words, comprehension of semantics, and grasping linguistic nuances. Undoubtedly, this is a groundbreaking approach.